2021
DOI: 10.1002/ags3.12446
|View full text |Cite
|
Sign up to set email alerts
|

The current status and future directions of robotic pancreatectomy

Abstract: Robotic distal pancreatectomy (RDP) and robotic pancreatoduodenectomy (RPD) were first described in 2002 and 2003, respectively. 1,2 Several systematic reviews and cohort studies have subsequently shown that robotic pancreatectomy has better or comparable perioperative outcomes compared with conventional open or laparoscopic pancreatectomy. Therefore, in the future, robot pancreatectomy could become an alternative to conventional surgery; however, its use is still controversial. To promote a better understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…57,60 Prehabilitation for at least 4 weeks prior to surgery might be nec- open surgery, in terms of less postoperative pain, early postoperative recovery, lower complications, and mortality rates in resections of gastrointestinal tract [61][62][63][64] and HBP cancers. [65][66][67][68] However, the impact of minimally invasive surgery in frail patients remains uncertain.…”
Section: Effec Ts Of Pre-or Rehab Ilitation On Perioper Ative Outcome...mentioning
confidence: 99%
See 1 more Smart Citation
“…57,60 Prehabilitation for at least 4 weeks prior to surgery might be nec- open surgery, in terms of less postoperative pain, early postoperative recovery, lower complications, and mortality rates in resections of gastrointestinal tract [61][62][63][64] and HBP cancers. [65][66][67][68] However, the impact of minimally invasive surgery in frail patients remains uncertain.…”
Section: Effec Ts Of Pre-or Rehab Ilitation On Perioper Ative Outcome...mentioning
confidence: 99%
“…Minimally invasive surgery, including laparoscopic or robotic surgery, has been shown to improve postoperative outcomes, compared to open surgery, in terms of less postoperative pain, early postoperative recovery, lower complications, and mortality rates in resections of gastrointestinal tract 61 , 62 , 63 , 64 and HBP cancers. 65 , 66 , 67 , 68 However, the impact of minimally invasive surgery in frail patients remains uncertain.…”
Section: Minimally Invasive Surgery For Frail Patients With Gastroint...mentioning
confidence: 99%
“…Robotic surgery is dramatically becoming widespread in the field of pancreatic surgery because of its technical advantages including high optical magnification and articulation of forceps. 1,2 Despite these advantages, the surgical field tends to be narrow due to the high magnification, and the forceps have no tactile sensation. It is possible to supplement the sense of touch with visual information within the surgical field, but outside the surgical field, there is no tactile information at all.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery is dramatically becoming widespread in the field of pancreatic surgery because of its technical advantages including high optical magnification and articulation of forceps 1,2 . Despite these advantages, the surgical field tends to be narrow due to the high magnification, and the forceps have no tactile sensation.…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort studies reported by high-volume international centers as well as systematic reviews conclude that robotic distal pancreatectomy (RDP) has better or comparable surgical outcomes as laparoscopic distal pancreatectomy (LDP). [1][2][3][4][5] Hence, it is expected that in the future, RDP rather than LDP will be applied for a tumor located in the pancreatic body or tail. However, local hospitals in Japan not only have fewer experienced surgeons with Japanese hepatobiliary-pancreatic (HBP) certification but also perform fewer pancreatectomies compared with urban hospitals.…”
mentioning
confidence: 99%